الاستراتيجية التوجيهية في سورة الأحزاب -مقاربة تداولية - بكوش, سميرة; زكور, كريمة (جامعة الوادي - university of Eloued, 2023)
تنبني الاستراتجية الخطابية على عدة عوامل ذات الأثر البالغ في استعمال اللغة و تأويلها،ومن ذلك أثرها في توجيه المرسل لاختيار استراتجية مناسبة للسياق وهي أنواع: التضامنية، التلمحية ، الاقناعية ، التوجيهية؛ مختارين الاستراتجية التوجيهية موضوع دراساتنا في سورة الأحزاب (أنموذجا)–مقاربة تداولية- حيث تعتبر عاملا مهما في إتمام سيرورة العملية التواصلية بشكل صحيح مؤدية غرضها التوجيهي التواصلي يتمثل في (المقصدية/السلطة) المتكلم بواسطة التعبيرعنها بآليات لغوية مختلفة كالأمر، والنهي، والنداء، والاغراء، وألفاظ المعجم... تستخدم حسب متلطبات ظروف الخطاب التي تؤثر في المتلقي وتلزمه بفعل القيام في إنجاز شيء معين The rhetorical strategy is built upon several factors that greatly influence language usage and interpretation. One of these factors is its impact on guiding the sender to choose an appropriate strategy for the context. These strategies include solidarity, allusion, persuasion, and directive strategies. In our study, we have chosen the directive strategy as the subject of our analysis in Surah Al-Ahzab as a case study, using a discursive approach. This strategy is considered an important element in completing the communicative process correctly, with its communicative objective being directive power exerted by the speaker through various linguistic mechanisms such as commands, prohibitions, appeals, temptations, and lexical expressions. These mechanisms are used based on the requirements of the speech situation, which influence the receiver and obligate them to perform a specific action.
لسانيات عامة
Keywords: الاستراتجية الخطابية، الاستراتجية التوجيهية، سورة الأحزاب، المقصدية، السلطة، السياق: rhetorical strategy, directive strategy, Surah Al-Ahzab, communicative objective, power, context